Pros and cons of e-learning in economics and business in Central and Eastern Europe: Cross-country empirical investigation - Agnieszka Głodowska; Krzysztof Wach; Blaženka Knežević (Business Systems Research (BSR), 2022)
Background: The ongoing information and technological revolution, as well as the Covid-19 pandemic, accelerated the use of e-learning worldwide. Objectives: This article aims to present the results of our empirical research among students of economics and business from Central and Eastern Europe on the advantages and disadvantages of e-learning. Methods/Approach: The article uses a survey, and the research sample included 1647 respondents (students of economics and business) from universities in three countries: Croatia, Poland, and Serbia. We used the multivariate comparative analysis (factor analysis and principal components analysis) by applying Statistica computer software. Results: The assessment of individual forms of e-learning in the three countries is similar. In e-learning, investigated students appreciated, first of all, the time-saving. At the same time, it is difficult to concentrate and harder to develop the interpersonal skills needed to work in a real environment. Conclusions: E-learning seems to be a vital instrument complementing traditional learning, as the respondents declared. However, it should not replace traditional face-to-face education; it should only support it.
Keywords: A22; A23; I23; 330; e-learning; distance learning; factor analysis; Croatia; Poland; Serbia